Pembiayaan Pembangunan Perkotaan Melalui Pemanfaatan Instrumen Keuangan - Hirawan, Susiyati B. (Center for Research and Community Services ITB, 1995)
Cities in Indonesia, in the future, will be facing challenges to reduce and eliminate the disparities between the heed of infrastructure investment and urban services with limited state financial ability to fulfill it. Some government opportunities and potencies, especially that are related to the mobilization of revenue sources which have been utilized by regional government, are still conventional in nature, such as tax, retribution and loans. Some facts have shown that outside those sources there are other non-conventional sources that are potential to be used, such as betterment levies, development impact fees, excess condemnation, obligation, and concession.